2000
DOI: 10.1007/s005860000144
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between epidural fibrosis, pain, disability, and psychological factors after lumbar disc surgery

Abstract: Failed back surgery syndrome (FBSS) is an important complication of lumbar disc surgery. Epidural fibrosis is one of the major causes of FBSS. However, most patients with epidural fibrosis do not develop symptomatic complaints from scarring. The purpose of this prospective study was to evaluate the relationships among the severity of epidural fibrosis, psychological factors, back pain and disability after lumbar disc surgery. Twenty-nine surgically managed patients (13 women, 16 men) were included in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
1
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 23 publications
3
53
1
12
Order By: Relevance
“…Most of the published literature is on lumbar discectomy complications, such as postoperative wound hematoma, neuronal injury (including postoperative dysethesia), recurrent herniation, postoperative instability, wrong level of exposure, arachnoiditis, infection, incidental durotomy (including its long term sequelae), and pseudomeningoceles 1,2,5,9,18,26,35,[38][39][40]47,49,51,53,54) . In addition, there have been case reports of rare complications after lumbar discectomy, such as development of an arteriovenous fistula, major vessel injury, epidural fibrosis, ureteral injury, compartment syndrome with acute renal failure, iliac artery injury, intradural disc migration, bowel injury, septicemia, symptomatic pneumorachis, instrument failure, postoperative radicular neuroma, Ogilvie's syndrome, and reflex sympathetic dystrophy 3,4,10,12,13,[15][16][17]19,21,22,34,36,37,41,44,45,48,52) . In reports on cases subsequent to full endoscopic discectomy, published complications have included recurrent disc herniation on the same side, incomplete removal of a ruptured disc, infection, neuronal injury (including sensory changes), dural tears, vascular injury, psoas hematoma, and sympathetically mediated pain [6][7][8]11,14,[23][24][25]…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published literature is on lumbar discectomy complications, such as postoperative wound hematoma, neuronal injury (including postoperative dysethesia), recurrent herniation, postoperative instability, wrong level of exposure, arachnoiditis, infection, incidental durotomy (including its long term sequelae), and pseudomeningoceles 1,2,5,9,18,26,35,[38][39][40]47,49,51,53,54) . In addition, there have been case reports of rare complications after lumbar discectomy, such as development of an arteriovenous fistula, major vessel injury, epidural fibrosis, ureteral injury, compartment syndrome with acute renal failure, iliac artery injury, intradural disc migration, bowel injury, septicemia, symptomatic pneumorachis, instrument failure, postoperative radicular neuroma, Ogilvie's syndrome, and reflex sympathetic dystrophy 3,4,10,12,13,[15][16][17]19,21,22,34,36,37,41,44,45,48,52) . In reports on cases subsequent to full endoscopic discectomy, published complications have included recurrent disc herniation on the same side, incomplete removal of a ruptured disc, infection, neuronal injury (including sensory changes), dural tears, vascular injury, psoas hematoma, and sympathetically mediated pain [6][7][8]11,14,[23][24][25]…”
Section: Discussionmentioning
confidence: 99%
“…The formation of postoperative epidural fibrosis is an inevitable result of laminectomy. Although the relationship between epidural fibrosis and clinical symptoms of FBSS has not been unequivocally proven, as many as 24% of all FBSS cases may be attributed to epidural scar adhesion [27].The mechanical tethering of nerve roots, or the dura, by the excessive formation of epidural fibrosis may be a contributing factor for a significant subset of patients suffering from FBSS [3,26,27]. However, several authors have reported that there are no important differences between symptomatic and asymptomatic patients in fibrosis demonstrated by computed tomography (CT) and magnetic resonance imaging (MRI).…”
Section: Discussionmentioning
confidence: 99%
“…При этом предполагаемый мор-фологический субстрат боли часто не диагностируют. Сохраняющиеся вертеброгенные боли в послеопера-ционном периоде могут быть вызваны многими причинами, одна из которых, наиболее распространенная, обуслов-лена формированием рубцовых спа-ек в перидуральном пространстве [3,12]. Невральные структуры могут быть подвержены как прямой компрессии рубцовой тканью, так и опосредован-ной: сдавление вен в эпидуральном пространстве приводит к их расши-рению, что, в свою очередь, вызы-вает компрессию нервной ткани [6,26].…”
unclassified
“…Однако многочисленные исследования показали, что транс-плантированная жировая ткань также склонна к фиброзному перерождению и не снижает риска болевого синдро-ма в послеоперационном периоде. Результаты большей части исследо-ваний такого рода не продемонстри-ровали статистически значимых раз-личий по сравнению с контрольны-ми группами и не выявили признаков уменьшения объема формирующейся рубцовой ткани в перидуральном про-странстве [2,7,12,13].…”
unclassified